Liquid xenon scintillation measurements and pulse shape discrimination in the LUX dark matter detector - Akerib,DS; Alsum,S; Araujo,HM; Bai,X; Bailey,AJ; Balajthy,J; Beltrame,P; Bernard,EP; Bernstein,A; Biesiadzinski,TP; Boulton,EM; Bras,P; et al. (PHYSICAL REVIEW D, 2018)
Weakly interacting massive particles (WIMPs) are a leading candidate for dark matter and are expected to produce nuclear recoil (NR) events within liquid xenon time-projection chambers. We present a measurement of the scintillation timing characteristics of liquid xenon in the LUX dark matter detector and develop a pulse shape discriminant to be used for particle identification. To accurately measure the timing characteristics, we develop a template-fitting method to reconstruct the detection times of photons. Analyzing calibration data collected during the 2013–2016 LUX WIMP search, we provide a new measurement of the singlet-to-triplet scintillation ratio for electron recoils (ER) below 46 keV, and we make, to our knowledge, a first-ever measurement of the NR singlet-to-triplet ratio at recoil energies below 74 keV. We exploit the difference of the photon time spectra for NR and ER events by using a prompt fraction discrimination parameter, which is optimized using calibration data to have the least number of ER events that occur in a 50% NR acceptance region. We then demonstrate how this discriminant can be used in conjunction with the charge-to-light discrimination to possibly improve the signal-to-noise ratio for nuclear recoils.